Morbidity and mortality in Methanol Poisoning: An Observational Study conducted in Karachi - Sattar, Rukhsana; Sultan, M Omer; Khan, Muhammad Inam; Kumar, Sham; Omer, Aasima; Amna (International Journal of Endorsing Health Science Research, 2016)
Background: Alcohol poisoning is a serious issue in both the developed and developing countries. Illicit alcohol is commonly called as moonshine or bootleg whereas in Pakistan it is ordinarily known as tharra, kuppi, desi sharab, or daroo. This alcohol is mainly prepared by fermenting the mash of sugar cane pulp in a clay pot up to near 100% alcohol, however, it may contain impurities and many toxic materials. The awareness and basic knowledge of methanol poisoning is quite scarce in our society due to the cultural aspects. The goal of our study is to identify the clinical factors associated with the alcohol poisoning along with the frequency of mortality. Methodology: A cross sectional has been conducted on the patients who were admitted in the National Poison Control Centre, Jinnah Postgraduate Medical Centre, Karachi. The patients who presented in a critical condition afterwards the alcohol consumption were included in the study from the year 2011 to 2015. Results: The inclusion criteria conscripted a total of 188 patients in the study amongst which majority was observed during a single outbreak in the month of September 2011. The results of the study recorded mortality in 38.83% of the study group while 35.64% indicated survival with sequelae. On the other hand, 25.53% of the patients were discharged with recovery. Conclusion: Morbidity in the cases of methanol poisoning tends to be crucial and high along with an eminent rate of mortality. Sequelae from methanol poisoning predominantly involves the visual disturbances including the blindness.